Formação de professores no Uruguai: tensões e desafios do processo de transição para um modelo universitário de formação de ensino - Zidán, Eduardo Rodríguez; Silva, Javier Grilli; Rodríguez, Soledad Rodríguez (Formação Docente – Revista Brasileira de Pesquisa sobre Formação de Professores, 2020)
Uruguay has initiated in recent years a complex process of renewal in the training of education professionals. In this sense, the transition to a teacher training of a university nature highlights the conflict between formative traditions and the new demands of teacher policies that seek to rethink the required skills, knowledge and working conditions of teachers. This report aims to deepen the current process of transformation of the model of training of teachers of secondary education in Uruguay, from a historical and analytical perspective. The approach of this process is carried out from a double way of analysis. On the one hand, it is studied the genesis and the main milestones of the education of secondary school teachers in Uruguay. In parallel, we reflect on the main tensions and conflicts that arise from the analysis of the implementation of educational policies and the different positions and conflicts between administrative authorities, trade unions and different teaching groups. Among other aspects that generate tensions and conflicts in the history of teacher training in the country, we reflect on the debate around the design of curricular plans, regulations of training processes and teacher training practices.